New Tatar Settlements in Lower Tara Area in Last Third of 19th Century: Foundation History, Population Structure, and Livelihoods - M. N. Tikhomirova; K. N. Tikhomirov (Научный диалог)
The article is dedicated to the history of the establishment of the villages of Malye Murly in the Tarsky District and Molodtsovo in the Muromtsevsky District of the Omsk Region, founded by Tatars during the period of mass migrations to Siberia. These villages no longer exist. The paper introduces documents from regional archives into scholarly discourse. Materials from the First All-Russian population census of 1897 have been analyzed to study the age, gender, and ethnic composition of the inhabitants. The article reconstructs the economic activities of the settlers. The authors conclude that the village of Malye Murly (also known as Novo-Murlinskaya) was established by Tatars from Ust-Tarskaya in the 1870s, while Molodtsovo (also known as Molodtsovsky settlement) was settled by residents of the Chipliarovski yurts prior to 1897. It is reported that both settlements lasted for about a century. Evidence suggests that the inhabitants of both settlements engaged little in agriculture; they had more developed livestock practices but lacked sufficient land resources, as the best lands were occupied by older settlements or belonged to the state. The authors conclude that in their formative stages, these settlements exhibit similar characteristics to another Tatar village, Mamshenkino in the Bolsherechensky District of Omsk Region, which was also founded during this period and whose residents eventually dispersed.